First Case of Dirofilariasis in a Dog From Goa, India - Das, Nikita Sunil; Pawar, Prashant Dhanaji; Mhase, Prashant Patilba; Sarawade, Vrushali Namdev; Dhaygude, Vitthal Shrirang; Kumar, Hemant; Singla, Lachhman Das (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Dirofilariosis caused by a filaroid nematode Dirofilaria immitis is a severe disease condition in canines transmitted through mosquitoes and flea bites (Borthakur et al., 2015).